Program Belajar Mengaji Al-Qur’an dalam Menanamkan Karakter Islami pada Anak di Desa Lakambau Kabupaten Buton Selatan - Abdul Rahim; Widyastuti Widyastuti; Nur Nazli; Felnia Felnia (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2022)
Reading the Al-Qur'an is one of the religious practices which is a good practice with the hope of being able to read the Al-Qur'an accurately, with tartil, and with good pronunciation. To form an Islamic character by being able to create the character of the Qur'an, it is also important to get used to reading the Qur'an. The method in this service is a persuasive method for recitation participants, then the children are given material about planting Islamic characters, so that children can learn to read the Koran. Providing guidance to children in the process of this activity is carried out by providing Islamic character material to children, as well as teaching reading the Qur'an, so that children in Lakambau Village can maximize their academic work activities at the University of Muhammadiyah Buton. The results of the participants' posttest showed that participants reached the high category of 10 people or 66.67%, the medium category was 4 people or 26.66%, while the low category was 1 person or 6.67%. The conclusion in this service is that children are very enthusiastic about participating in the Al-Qur'an learning activity program, so that students can instill Islamic character in children in Lakambau Village, South Buton Regency.